UPAYA PENYELESAIAN WANPRESTASI ATAS PINJAMAN KREDIT DENGAN JAMINAN SK PNS (STUDI PADA BANK MANDIRI KCP MEDAN WAHIDIN) - Siallagan, Praja Yudha Balista; Kaban, Maria; Sembiring, Idha Aprilyana (Fakultas Hukum Universitas Sriwijaya, 2024)
Abstract : One form of credit provided to civil servants (PNS) is the Fixed Income Credit Group (KRETAP). The Civil Servant Certificate (SK PNS) can be used as collateral for bank loans, as it is considered an acceptable form of security by several banks. However, the process of granting credit loan facilities can encounter obstacles, one of which is the borrower's default in paying installments. Therefore, this thesis is entitled